Heritability Estimate for Antibody Response to Vaccination and Survival to a Newcastle Disease Infection of Native chicken in a Low-Input Production System - Hako Touko, Blaise Arnaud; Kong Mbiydzenyuy, Anold Tatah; Tumasang, Tebug Thomas; Awah-Ndukum, Julius (Frontiers in Genetics, 2021)
The Newcastle disease virus (NDV) is the deadliest chicken pathogen in low input village poultry and selecting for NDV resistance has been recommended as a sustainable strategy in backyard poultry production systems. However, selecting for disease resistance need precision data on either a big population sample size or on many generations with good pedigree records for effective prediction of heritability and breeding values of the foundation stock. Such conditions are almost impossible to be met in low-input systems. This study aimed at proposing a realistic method for estimating the heritability of the immune response to vaccination and survival to NDV infection in village poultry production in Cameroon. A 1% and 3% selection intensity of cocks and hens for higher antibody response to vaccination followed by progeny selection of chickens who survived an experimental NDV infection was conducted from an initial population of 1702 chickens. The selection induced an increase of 1012.47 units/ml (P<0.01) of the NDV antibody of the progeny as well as an effective survival rate increase of 11.75%. Three methods were used to estimate the heritability of NDV antibody response to vaccination. h^2 was moderate irrespective of the method with estimates of 0.2227; 0.2442 and 0.2839 for the breeder’s equation method, the graphical method, and the full-sib/half-sib nested design respectively. The mortality rate of infected chickens was high (86%). The effect of the genetic type and sex were significant (P<0.05) for the effective survival rate to NDV infection with Naked neck chickens recording ESR of 14% against 2.25% for the normal feather type. A very low heritability (0.0891) was observed for survival against NDV infection. We confirm the evidence of disease resistance and the effect of the selection for antibody response to vaccination on the improvement of the survival against NDV disease. While the full sib-half sib nested design is more appropriate in case of availability of pedigree information, the direct methods are still useful in case of unavailability of full pedigree information. It is recommended that gene expression analysis should be prioritized for disease resistance assessment and selection of native breeds of poultry